C \ in a nutshell - Dayton, Peter; Albahari, Ben; Neward, Ted (Beijing : O'Reiling, 2003)
Computer Science
Keywords: C \ programming language; Introducing C; Net framework; Advanced C features; String handling; Networking; Assembling; Memory mangement; Threding; Diagnostics; Customer attributes